ACTIVITY OF INTERNATIONAL FINANCIAL INSTITUTES AND THEIR PARTICIPANTS OF THEIR RELATIONS WITH UKRAINE - Швайко, М. Л. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article deals with the peculiarities of the activities of international financial institutions and their relationship with Ukraine in modern conditions. The main goals and directions of the activities of key international financial institutions, such as the International Monetary Fund, the World Bank, are specified. It is noted that in the context of globalization their role and significance grows, because they are supranational regulators that affect financial security of both the individual countries of the world and security of the world financial market as a whole. The main reasons for the emergence of international financial institutions and the basic goals of their activities are systematized. The International Monetary Fund is the main international financial institution, which is the institutional basis of the world monetary and financial system. The IMF assesses the sufficiency of the global financial protection system, provides economic supervision and control over the safe operation of the global monetary and financial system, and should respond to emerging problems and imbalances in a timely manner, providing the necessary funding and technical assistance to countries under the approved arrangements. The analysis of the statistics on loans provided by the IMF within various lending mechanisms, the analysis of the state of the world ’s debts to the IMF in the context of its privileged and non – beneficial loans, the peculiarities of the IBRD’ s relations with the member countries are analyzed and there are identified current trends in this direction. The key problems and challenges in the work of international financial institutions are formulated and prospective ways of their development are defined, the use of which will promote both optimization of their activities and strengthening the security of the world financial market.